1988
DOI: 10.1029/ja093ia12p14611
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic model for equatorial spread F, 1, Model description and application to electric field and neutral wind effects

Abstract: Linear growth rates for the gravitational Rayleigh‐Taylor instability are calculated using the ionospheric electron density distribution obtained by solving the ion continuity equations including dynamics for O+, NO+, O2+, and N2+ ions. The instability model includes the contributions from plasma away from the magnetic equatorial plane. Effects of the transequatorial component of the thermospheric wind and the E × B drift are investigated. Thermospheric winds are based on theoretical calculations. The E × B dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
190
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(203 citation statements)
references
References 40 publications
12
190
1
Order By: Relevance
“…Figures 5 and 6 show that the equinoctial upward drifts are generally large enough for exciting strong spread F. On the other hand, the small upward drifts and early reversal times during June solstice do not allow for enough wave growth prior to the damping due to the large downward drifts so that the narrow low-altitude unstable layers rarely develop into wide high-altitude strong scattering layers. During December solstice, the large evening upward drifts, the late reversal time, and the small early night downward drifts provide the most favorable conditions for the generation of fully developed strong and longer lasting scattering layers over Jicamarca, as shown earlier by Maruyama [1988]. However, when there are unusually large downward drifts in the early night period (due to westward prompt penetration electric fields, for example) during this season, the unstable layers rapidly weaken and disappear, as illustrated in ' ' ' i , , , , i • , , , i , , , The right-hand panels in Figure 6 show the effects of enhanced magnetic activity over periods of at least 6 hours on the prereversal velocity enhancements and occurrence of spread F. This criterion highlights the effect of disturbance dynamo electric fields since prompt penetration electric fields (driven by sudden changes in the high-latitude convection) are equally likely to increase and decrease the evening upward velocities [e.g., Fejer and Scherliess, 1997].…”
Section: Spread F During Premidnight Hoursmentioning
confidence: 85%
See 1 more Smart Citation
“…Figures 5 and 6 show that the equinoctial upward drifts are generally large enough for exciting strong spread F. On the other hand, the small upward drifts and early reversal times during June solstice do not allow for enough wave growth prior to the damping due to the large downward drifts so that the narrow low-altitude unstable layers rarely develop into wide high-altitude strong scattering layers. During December solstice, the large evening upward drifts, the late reversal time, and the small early night downward drifts provide the most favorable conditions for the generation of fully developed strong and longer lasting scattering layers over Jicamarca, as shown earlier by Maruyama [1988]. However, when there are unusually large downward drifts in the early night period (due to westward prompt penetration electric fields, for example) during this season, the unstable layers rapidly weaken and disappear, as illustrated in ' ' ' i , , , , i • , , , i , , , The right-hand panels in Figure 6 show the effects of enhanced magnetic activity over periods of at least 6 hours on the prereversal velocity enhancements and occurrence of spread F. This criterion highlights the effect of disturbance dynamo electric fields since prompt penetration electric fields (driven by sudden changes in the high-latitude convection) are equally likely to increase and decrease the evening upward velocities [e.g., Fejer and Scherliess, 1997].…”
Section: Spread F During Premidnight Hoursmentioning
confidence: 85%
“…These observations have determined the dependence of the F region plasma drifts on season, solar cycle, and magnetic activity. Maruyama [1988] showed that the effect of the vertical drift velocity on the growth rate of the Rayleigh-Taylor instability can explain the winter-summer asymmetry of spread F occurrence over Jicamarca during solar maximum. Kelley and Maruyama [1992] presented case studies of storm-time electric field effects on the generation of equatorial spread F over Jicamarca during postmidnight hours and tested the assumption that the penetration of eastward plasmaspheric electric fields initiates the generation of these irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…The ESF studies using ionosonde data (Sales et al, 1996;Stephan et al, 2002;Whalen, 2002), the Global Positioning System (GPS) (Aarons et al, 1996;Mendillo et al, 2000Mendillo et al, , 2001, radars (Woodman and LaHoz, 1976;Hysell and Burcham, 1998), satellite (Huang et al, 2001;Su et al, 2001), and numerical modeling (Maruyama, 1988;Sultan, 1996) have demonstrated the general morphology of the ESF phenomenon. Now, it is known that there are some candidate mechanisms helping the ESF development.…”
Section: Introductionmentioning
confidence: 99%
“…4). During the equinoctial months, a larger dh F /dt and a higher BSSF occurrence rate indicate that a larger upward drift lifts the F-layer to higher altitudes, which not only results in a favorable condition for the GRT instability but also causes an E×B drift instability (Maruyama, 1988;Kelley, 1989). In contrast, the small dh F /dt value and the lower occurrence in the winter months suggest that the F-layer is not raised to an altitude high enough to generate instabilities.…”
Section: Seasonal Variation In Dh F /Dtmentioning
confidence: 99%
“…Additionally, during the summer months, the highest BSSF occurrence and the mean values of dh F /dt, 20-27 m/s, suggest that another mechanism would also help the BSSF formation. In addition, the late reversal time of the upward drift velocity should be another reason to account for the highest occurrence probability at December solstice, because the late reversal time is favorable for the development of strong scattering layers in the F-region (Maruyama, 1988;Fejer et al, 1999).…”
Section: Seasonal Variation In Dh F /Dtmentioning
confidence: 99%